2012
DOI: 10.1016/j.kjms.2012.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risks of esophageal cancer in Taiwanese men

Abstract: This study aims to explore whether certain occupations were associated with the risk of esophageal squamous cell carcinoma (ESCC) in Taiwan. In a hospital-based case-control study, we collected 326 newly diagnosed ESCC patients and 386 age-matched controls (the ratio of case patients: controls = 1:1-2). All respondents completed a questionnaire, including 33 occupations in which environments potential exposure to cancer-related hazards are present. Workers with dust and metal exposure were categorized into Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
8
2
Order By: Relevance
“…[12][13][14][15][16][17][18][19] Increased risks of oesophageal AC and/or SCC among chemical process workers, chimney sweeps, printers, painters, food workers, waiters and cooks and stewards were similarly observed in this study. However, the increased risks of oesophageal cancer among health professionals, 20 farmers, gardeners and agricultural workers 21,22 observed in other studies is in contrast with the decreased risks observed in this study for these occupational categories.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19] Increased risks of oesophageal AC and/or SCC among chemical process workers, chimney sweeps, printers, painters, food workers, waiters and cooks and stewards were similarly observed in this study. However, the increased risks of oesophageal cancer among health professionals, 20 farmers, gardeners and agricultural workers 21,22 observed in other studies is in contrast with the decreased risks observed in this study for these occupational categories.…”
Section: Discussioncontrasting
confidence: 99%
“…Some of the findings of this study were not consistent with those of previous studies. Indeed, increased risks of oesophageal cancer among farmers, gardeners and agricultural workers were observed in Taiwanese 21 and Brazilian 22 studies, whereas decreased risks were observed in this study. A nationwide Swedish population-based case-control study found an increased risk of oesophageal SCC among health service and nursing workers based on a small number of observed cases (N 5 6), 23 whereas the present study found decreased risks in similar occupational categories.…”
Section: Discussioncontrasting
confidence: 47%
“…There is no consistent finding regarding the association between herbicides, pesticides and risk of oesophageal carcinoma. However, in a study conducted in Taiwan, being a farmer was significantly associated with the increased occurrence of oesophageal cancer (60) .…”
Section: Discussionmentioning
confidence: 99%
“…27 For instance, farming, gardening, and agricultural works have been linked to an increased risk of OC in Taiwan and Brazil. 28,29 Being farmers and exposure to herbicides were found to have significant positive associations with oesophageal carcinoma. 30,31 Furthermore, a growing body of evidence has shown a strong relationship between exposure to heavy metals, Poly Aromatic Hydrocarbons (PAHs)emitted from firewood, and increased risk of oesophageal cancer.…”
Section: Introductionmentioning
confidence: 95%